Shades of gray - Kessler, Jackie (Jackie H.) (Icarus Project, 2010)
When the most dangerous man alive, the sociopath known as Doctor Hypnotic, suddenly surfaces, superheroes Jet and Iridium will once again be called upon to set aside their differences. Yet in the process, deeply buried secrets will come to light that will change everything the former best friends think they know about each other and themselves.